Crucial Roles for SIRT2 and AMPA Receptor Acetylation in Synaptic Plasticity and Memory - Wang, Guan; Li, Shaomin; Gilbert, James; Gritton, Howard J.; Wang, Zemin; Li, Zhangyuan; Han, Xue; Selkoe, Dennis J.; Man, Heng-Ye (Cell reports (Cambridge), 2017)
AMPA receptors (AMPARs) mediate fast excitatory synaptic transmission and are crucial for synaptic plasticity, learning, and memory. However, the molecular control of AMPAR stability and its neurophysiological significance remain unclear. Here, we report that AMPARs are subject to lysine acetylation at their C termini. Acetylation reduces AMPAR internalization and degradation, leading to increased cell-surface localization and prolonged receptor half-life. Through competition for the same lysine residues, acetylation intensity is inversely related to the levels of AMPAR ubiquitination. We find that sirtuin 2 (SIRT2) acts as an AMPAR deacetylase regulating AMPAR trafficking and proteostasis. SIRT2 knockout mice (Sirt2−/−) show marked upregulation in AMPAR acetylation and protein accumulation. Both Sirt2−/− mice and mice expressing acetylation mimetic GluA1 show aberrant synaptic plasticity, accompanied by impaired learning and memory. These findings establish SIRT2-regulated lysine acetylation as a form of AMPAR post-translational modification that regulates its turnover, as well as synaptic plasticity and cognitive function. [Display omitted] •AMPA receptors are subject to lysine acetylation within their C-terminal domains•Acetylation increases AMPA receptor stability and reduces receptor trafficking•SIRT2 causes deacetylation of AMPA receptors and regulates receptor protein stability•Elevated acetylation of AMPA receptors leads to impaired synaptic plasticity and memory Stability of glutamatergic AMPA receptors in neurons is of vital importance for synaptic transmission and brain function. Wang et al. report that AMPA receptors are subject to acetylation, which is regulated by sirtuin 2 and controls receptor trafficking, turnover, synaptic plasticity, and memory.